2022
DOI: 10.3389/fbioe.2022.922772
|View full text |Cite
|
Sign up to set email alerts
|

Latest Trends in Lateral Flow Immunoassay (LFIA) Detection Labels and Conjugation Process

Abstract: LFIA is one of the most successful analytical methods for various target molecules detection. As a recent example, LFIA tests have played an important role in mitigating the effects of the global pandemic with SARS-COV-2, due to their ability to rapidly detect infected individuals and stop further spreading of the virus. For this reason, researchers around the world have done tremendous efforts to improve their sensibility and specificity. The development of LFIA has many sensitive steps, but some of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 155 publications
0
21
0
Order By: Relevance
“…A common strategy of LFA is the use of antibodies as the detection agents, which is called a lateral flow immunoassay (LFIA). In this method, the detection label, often AuNPs, is lined with antibodies to recognize the antigens to be detected [ 80 ]. As the light absorption of AuNPs is in the visible region around 520 nm, they are visible to the eye, thus making the assay widely accessible to the general public.…”
Section: Plasmonic Nanostructuresmentioning
confidence: 99%
“…A common strategy of LFA is the use of antibodies as the detection agents, which is called a lateral flow immunoassay (LFIA). In this method, the detection label, often AuNPs, is lined with antibodies to recognize the antigens to be detected [ 80 ]. As the light absorption of AuNPs is in the visible region around 520 nm, they are visible to the eye, thus making the assay widely accessible to the general public.…”
Section: Plasmonic Nanostructuresmentioning
confidence: 99%
“…53 There are recent reviews devoted to nanomaterials and their promising applications in LF, which are too wide to be included in this review. Refer to the reviews of Nguyen et al, 55 Sena-Torralba et al, 52 Vahid Shirshahi and Guozhen Liu, 56 and Mirica et al 57 for more information about novel nanomaterials employed in LF tests. It must be highlighted that gold nanoparticles (AuNPs; a.k.a.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Briefly, the physical principle of the LF assays is based on capillarity action. When the extracted specimen is added to the sample pad, the flow goes through the paper reaching the conjugate pad, where the nanoparticles (NPs) conjugated 57 with the bioreceptor are stored, ready to react to the target analyte (if present). Once the flow reaches the detection pad (membrane), if the specimen contains the target, the test line (TL) will appear indicating a positive result due to the presence of a specific bioreceptor that recognizes the target.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, most LFIAs functionalised with AuNPs are moderately sensitive and only provide qualitative information [ 12 ]. As an alternative to AuNPs, various reporters have been used in LFIAs, such as latex microparticles and europium nanoparticles [ 13 ]. Latex microparticles derived from polymer (commonly polystyrene) are used in LFIAs due to their unique colour flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…A report has shown that europium causes human safety issues such as respiratory tract, skin, and eye irritation. Furthermore, the synthesis method of these nanoparticles has some disadvantages, in that the obtained nanoparticles were normally not well dispersed, and discarding assays is not environmentally safe [ 13 ].…”
Section: Introductionmentioning
confidence: 99%